2010
DOI: 10.1620/tjem.222.141
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decrease in Inferior Vena Cava Diameter Measured with Echocardiography

Abstract: The diameter of the inferior vena cava (IVC) measured with echocardiography is clinically used as a parameter to estimate right atrial pressure, which reflects dehydration or overhydration. Because elderly patients fall easily into dehydration, normal values for IVC diameters in elderly patients may be helpful for geriatric medicine. However, normal values of IVC diameter in relation to age have not been investigated. The purpose of this study was to elucidate age-related changes in IVC diameter using echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 11 publications
2
25
1
5
Order By: Relevance
“…Here, however, examination of the cutoff points in the higher and lower BSA groups revealed that optimal cutoff points for the identification of elevated RAP varied between the two groups. Similar to a prior study of patients without cardiac disease, 16 we also found a positive correlation between BSA and IVC size in patients with various forms of cardiac disease. These findings support the concept that the IVC size is affected by body size and the need for splitting cutoff points for predicting abnormal RAP in relation to BSA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here, however, examination of the cutoff points in the higher and lower BSA groups revealed that optimal cutoff points for the identification of elevated RAP varied between the two groups. Similar to a prior study of patients without cardiac disease, 16 we also found a positive correlation between BSA and IVC size in patients with various forms of cardiac disease. These findings support the concept that the IVC size is affected by body size and the need for splitting cutoff points for predicting abnormal RAP in relation to BSA.…”
Section: Discussionsupporting
confidence: 90%
“…16 In the present study, the higher BSA group consisted of an older population with a larger proportion of men. Moreover, gender was associated with IVC diameter, whereas age was not.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to our findings, Masugata et al [12] found that age was accompanied by an increase in ΔDIVC in Japanese people in 2010. The authors suggest that low right atrial pressure and decreased IVC compliance in the elderly may have led to their results.…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
“…However, accurate data A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 6 on the effects of individual patient characteristics such as age, body mass index (BMI) and body surface area (BSA) on IVC parameters are lacking. Masugata et al (2010) reported an age-related reduction in maximum IVC diameter and an increase in the respiratory variation of IVC [12], but the participants in their study were older patients [15]. However, there has been little subsequent investigation of the utility of the index in evaluating volume status in either children or adults [16].…”
Section: Introductionmentioning
confidence: 96%
“…Masugata et al 32 investigated 200 patients from ages of 17e94 years old and found that increasing age was associated with reduced IVC diameter but increased IVC-CI. This may be due to physiological changes of the IVC wall.…”
Section: Changes Of the Ivc With Agementioning
confidence: 99%